Evaluation of devices to enhance miner self-escape in smoke-filled entries - SME Transactions 2011 - S. P. Harteis; D. W. Alexander; L. L. Chasko; C. J. Slaughter (Society for Mining, Metallurgy & Exploration, 2011)
The Department of Health and Human Services (HHS), National Institute for Occupational Safety and Health (NIOSH), Office of Mine Safety and Health Research (OMSHR), with the assistance of cooperating underground mining operations and state agencies, has conducted research exploring devices and technologies that could be used to assist miners navigating through smoke and dust resulting from a fire or explosion. Recent events in mines confirm that smoke and dust can enter and contaminate mine escapeways, creating an atmosphere with severely reduced visibility. This reduced visibility results in substantially increased escape times, possible disorientation or confusion, and increased stress levels, and may prevent evacuation altogether. Tools or devices that assist miners in navigating through smoke-filled areas void of lifelines could make the difference in successful escape from the mine. This paper presents the results of OMSHR research to identify and evaluate tools and devices that could provide meaningful information to evacuating miners in areas with limited visibility and without the benefit of a lifeline.